Who watches YOU? An allegory of dataveillance and cyberstalking - Carvalho, Luiz Paulo; Oliveira, Jonice; Santoro, Flavia (Anais do Workshop sobre as Implicações da Computação na Sociedade (WICS); 2020: Anais do I Workshop sobre as Implicações da Computação na Sociedade, 2020)
How your openly published personal data in Online Social Networks are used by other people? Not only organizations and companies are interested in them. From a qualitative approach, we present a hermeneutic of an episode of the TV series YOU, building an allegory that exposes the potential for cyberstalking and dataveillance. The romanticization and naturalization of these phenomena is tensioned, they are based on ethically dubious intentions and a semiotic discourse harmful to social sustainability.